(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Indian classical music from its inception till date has gone through various phases of transformations and transitions so the sitar music is. In the process it has embraced and rejected a number of features with maintaining an absolute balance with the old age tradition. From physical structures, playing styles (baaj) to its place in the world of Indian music the instrument has gone through the sea changes in the musical history. In 20thand 21stcentury in the world of globalization with the course of economic flexibility and advancement of technology, society leads to the Incorporation of western values, ideas, technologies and institutions and commoditization of art and music. My thesis “The Stylistic evolution of sitar baaj in 20thand 21stcentury” aimed at the holistic research of different aspects of sitar music. The research will also try to unfold the musical and non-musical factors worked behind this process of transition.